Reconstruction of the Scientific Integration Model in Indonesia: The Offer of Qur'anic Epistemology - Abid Nurhuda (Journal of Social Science and Humanities, 2026)
This research stems from concerns about the deeply rooted dichotomy of knowledge within the Indonesian education system, where religious and general knowledge are often positioned separately, even in opposition to each other. This situation not only creates epistemological divisions but also weakens the nation's competitiveness in facing global challenges. This study offers a reconstruction model for scientific integration based on Qur'anic epistemology as an alternative that can present a more holistic, ethical, and relevant approach to the needs of the times. Using qualitative research methods based on literature reviews, this study critically examines the relationship between revelation, reason, and empirical experience, and places it within the context of the dynamics of contemporary Indonesian education and development. The results of the study indicate that Qur'anic epistemology has great potential to become a foundation for scientific integration, because it affirms the unity of knowledge sources, connects the transcendental dimension with empirical reality, and offers an ethical orientation for scientific development. This integration model encompasses epistemological, curricular, and institutional dimensions that together form a new scientific paradigm.